Reception Analysis of Overseas Students Against Family Conflict in â€œNgeri-Ngeri Sedapâ€ Movie - Dina Aprilia Royyanti; Arif Surya Kusuma (UM Purwokerto Press, 2023)
Film is one of the media that is considered effective for telling messages because it is easily received and well felt by the audience. The Ngeri-Ngeri Sedap movie presents a family conflict that the researcher will use as a background to see the formed reception. This study uses descriptive qualitative methods through the reception analysis approach of Stuart Hall's encoding-decoding model to determine the acceptance of messages received by overseas students regarding the family conflict in the Ngeri-Ngeri Sedap movie. Based on the decoding results of the research conducted, the audience actively creates meaning for family conflicts in the film. The results showed that most informants were in a dominant position who accepted that the film tell about family conflicts, especially conflicts between parents and children and between siblings. Meanwhile, some informants are in a negotiated position who see conflict in the form of wrong communication patterns but have their own perspective on the meaning in the film.